Three Women, Three Generations: An In-Depth Case Study of Language Retention and Shift in One Family from the Maltese Australian Community in Melbourne (Global Journal of Human-Social Science, 2024)
This paper analysis one family pertaining to the Maltese Australian community in Melbourne and investigates the retention of the Maltese language The Maltese Australian community is a small community that is getting smaller since migration from Malta to Australia has largely stopped Thus the Maltese language is spoken mostly by the first generation of immigrants who left the island after the Second World War seeking a better future The second generation born in Australia usually understands the language but lacks the opportunity or the will to speak the language except with members of the family The third generation raised in a multicultural country normally has very little fluency in the Maltese language The investigation is grounded in interview data gathered among a family of three generations of Maltese origin in Melbourne The findings of this research show that the aging population of the Maltese community and the dominance of the English language do not favour the retention of the Maltese language in the future With the end of the first generation of post-World War Two migrants and the emergence of the fourth and fifth generations probably there will be an absolute shift to English the de-facto national language of Australia
Keywords: language retention; language shift; language attitudes; family domain; english dominance; maltese australians